2009
DOI: 10.1016/j.crvi.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and antioxidant activities of two Phlomis species: A correlation study

Abstract: Two traditional Chinese medicines (Phlomis umbrosa Turcz. and Phlomis megalantha Diels), as well as five pure phenolic compounds (protocatechic, chlorogenic, benzoic, rosmarinic acid, and rutin) have been studied for antioxidant activities in acetone and methanol extracts from leaves. An HPLC method was developed to quantify the amounts of 14 phenolic compounds in the leaf extracts. The antioxidant capacities of the studied species are high. Almost all samples were capable of directly scavenging DPPH and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 25 publications
6
42
1
Order By: Relevance
“…Recently, interest has increased considerably in finding naturally occurring antioxidants for use in foods or medicinal materials to replace synthetic antioxidants [6] . It has been demonstrated that plants, containing high amounts of secondary metabolites like phenolic have been identified as a free radical or active oxygen scavengers and can prevent damages caused by oxidative stress [19][20][21] . Increasing experimental evidence has suggested that these compounds can affect a wide range of cell biological functions by virtue of their radical scavenging properties [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, interest has increased considerably in finding naturally occurring antioxidants for use in foods or medicinal materials to replace synthetic antioxidants [6] . It has been demonstrated that plants, containing high amounts of secondary metabolites like phenolic have been identified as a free radical or active oxygen scavengers and can prevent damages caused by oxidative stress [19][20][21] . Increasing experimental evidence has suggested that these compounds can affect a wide range of cell biological functions by virtue of their radical scavenging properties [6] .…”
Section: Discussionmentioning
confidence: 99%
“…High phenolic compounds from plant source lead to a positive activity as antioxidant. But this can be governed not only through the correlation coefficient but also through the scavenging activity in various antioxidant assays [20] . The antioxidant activity of the phenolic compounds was attributed to its redox properties, which allow them to act as reducing agents, hydrogen donators, singlet oxygen quenchers, and metal chelating property [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, the amount of flavonoid for these three species was reported to be 4.97, 4.11, and 1.99 (mg QE/g extract), respectively. Zhang and Wang [24] showed that the phenol contents of P. umbrosa and P. megalantha were 39.43 and 55.20 (mg GAE/g extract), respectively; also, the flavonoid contents were reported to be 7.12 and 35.91 (mg EE/g extract), respectively.…”
Section: Total Phenolics and Flavonoidsmentioning
confidence: 99%
“…This shows that the leaves have a stronger hydrogen donating capacity than the stems. Zhang and Wang [24] reported the IC 50 of P. umbrosa and P.megalantha to be 20.2 and 15.7 µg/ml, respectively; also, the IC 50 in P. caucasica, P. lanceolata, and P. aucheri was reported to be 0.1 mg/mL. [15] β-carotene/linoleic acid assay The methanolic extracts of the leaves and stems showed high antioxidant activity in β-carotene/ linoleic acid assay.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation